2015
DOI: 10.26719/2015.21.3.155
|View full text |Cite
|
Sign up to set email alerts
|

155 Investigating the informed consent process, therapeutic misconception and motivations of Egyptian research participants: a qualitative pilot study

Abstract: Few studies have explored the informed consent process among research participants in developing countries. This study aimed to evaluate the informed consent process, therapeutic misconception and motivation for participation among Egyptians participating in clinical trials. In a cross-sectional qualitative pilot study 103 participants in 10 clinical trials responded to a questionnaire. Over 90% agreed they had time to ask questions and received adequate information about the risks prior to consenting. All par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…We found that 50.0% of participants stated a desire to help others as a reason to enrol in research. This, however, contrasts with other studies showing that more than 90% stated a similar reason (9,12,13). Also, the chance to get better treatment was stated by only 41.1% of our respondents as a reason to participate in research.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…We found that 50.0% of participants stated a desire to help others as a reason to enrol in research. This, however, contrasts with other studies showing that more than 90% stated a similar reason (9,12,13). Also, the chance to get better treatment was stated by only 41.1% of our respondents as a reason to participate in research.…”
Section: Discussioncontrasting
confidence: 98%
“…In general, most of our participants expressed favourable attitudes towards research. For example, more than 90% believed that research was necessary to improve the health of society; similar findings regarding the importance of research have been reported in other studies from the Middle East (9,13). We found that 50.0% of participants stated a desire to help others as a reason to enrol in research.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Peculiarly, for many years papers on the matter originated almost exclusively from North America, but recently information on TM has emerged from more diverse populations including those with epilepsy in Finland3 and a broader group in Egypt,4 apparently reinforcing the idea that TM remains persistent. However, according to Kim et al , while TM is a serious problem when it occurs, this is not very often –it seems to be a real issue only in low numbers of the subjects that they have studied 5.…”
mentioning
confidence: 99%